CONSTRUCTING THE IDEOLOGY OF BEING A GOOD PERSON THROUGH THE CHARACTERS JIA BAOYU AND ODD IN DREAM OF THE RED CHAMBER AND FOUR REIGNS - Wang, Yelan; Patthranuprawat, Sayam (Journal of MCU Nakhondhat, 2026)
<audio class="audio-for-speech"></audio> The novels Dream of the Red Chamber and Four Reigns not only reflect the social contexts of Chinese and Thai societies, but also function as cultural spaces that reproduce moral ideologies defining the image of the “good person.” This article aims to analyze the ideology of being a good person and the mechanisms through which such an ideology is constructed, as represented by the characters Jia Baoyu in Dream of the Red Chamber and Aod in Four Reigns. The research employs documentary research and descriptive analysis, applying Louis Althusser’s concept of ideology as a theoretical framework for textual interpretation. In particular, it focuses on the concepts of interpellation and ideological state apparatuses to explain the role of social institutions in shaping and regulating characters to recognize and accept their positions within ideological structures. The findings reveal that the ideology of being a good person in both novels operates on three levels: the individual, the family, and society. Key mechanisms in the construction of this ideology include the education system, the family institution, and social norms. These mechanisms function to regulate, control, and interpellate characters, subtly guiding them to internalize moral values and social roles expected by society. These institutions function to guide, regulate, and interpellate characters into accepting moral values and social roles expected by society in a subtle yet powerful manner. However, the novels also expose the complexity and limitations of this process. Even when characters conform to socially endorsed ideals of goodness, they continue to encounter internal conflicts and the fragility of human existence. This research therefore expands the understanding of the role of classical novels as cultural spaces that not only reflect social realities but also participate in the reproduction, negotiation, and dynamic transformation of the ideology of being a good person across different cultural contexts.